A Self-tuning Grid Synchronization Method for Active Power Filters. Issue 17 (20th October 2016) - Ngo, Tuan; Biricik, Samet; Basu, Malabika
Abstract: This article introduces a new configuration for grid synchronization to detect the positive-sequence component of the voltage under unbalanced and distorted conditions. The proposed configuration is based on the frequency-locked loop technique and combines a self-tuning filter with a conventional second-order generalized integrator. The introduced structure is able to produce two orthogonal output signals for detecting grid voltage information. More importantly, it behaves as a high-order filter to completely remove harmonic components and still reserves benefits from the previous second-order generalized integrator methods. The grid magnitude and frequency are identified accurately and then provided to the active power filter for proper operations. Simulation and experimental results are presented to verify the concept of the introduced method. In addition, the performances of the proposed and conventional configurations are compared to recognize the significant improvements and effectiveness in the new method.